Optimization of Social Support in Physical Education Learning to Strengthen Students’ Social Self-Esteem - Blegur, Jusuf; Rajagukguk, Christin Prima Mery; Lumba, Andreas Johanis Fredik; Rosari, Renya (FKIP Universitas Lampung, 2021)
Optimization of Social Support in Physical Education Learning to Strengthen Students’ Social Self-Esteem. Objectives: This study aims to test the determination of teacher and classmate support for students’ social self-esteem. Methods: The participants were 94 junior high school students grade 7 (M = 12.7660; SD = 0.53733). We collected the data using The Teacher and Classmate Support Scale and Social Self-Esteem Inventory. Data were analyzed descriptively and the t-test. Findings: The results of teacher and classmate support and students’ social self-esteem variables show positive results, as well as proving that teacher and classmate support affects students’ social self-esteem during physical education learning activities. Conclusion: The presence of teachers in the learning class is necessary to provide social, emotional, and cognitive support to students so that they become more confident in performing their abilities and also feel comfortable with every performance they produce in some learning experiences and expressive learning cultures. Keywords: social support, teacher support, classmate support, students’ social self-esteem. DOI: http://dx.doi.org/10.23960/jpp.v11.i2.202105